Vegetarianism and the Older Adult - Kelly Johnston; Wendy Dahl (EDIS, 2019)
Vegetarian diets have become more and more popular in recent years, but there is a common concern that such a diet may not provide the adequate amount of nutrients. This 3-page document discusses this misconception and explains the various benefits of a vegetarian diet for older adults. Written by Kelly Johnston and Wendy J. Dahl and published by the UF/IFAS Department of Food Science and Human Nutrition, January 2019. http://edis.ifas.ufl.edu/fs317